Clinical manifestations, treatment, and outcomes of children and adolescents with eosinophilic esophagitis - Maraci Rodrigues; Maria Fernanda M. D'Amico; Fatima Regina Almeida Patiño; Dorina Barbieri; Aderson Omar Mourão Cintra Damião; Aytan M. Sipahi (Brazilian Society of Pediatrics, 2013)
Objective: This study aimed to describe the clinical, endoscopic, and histologic characteristics, as well as the response to conventional treatment of pediatric patients with the classical form of eosinophilic esophagitis (EoE). Methods: Study of clinical, laboratory, endoscopic, and histologic data and response to conventional treatment of 43 previously followed pediatric patients with the classical form of EoE. Results: A total of 43 patients diagnosed with EoE were included in the study, of which 37 were males (86%), with a mean age of 8.4 years. The most common symptoms were: nausea, vomiting, and abdominal pain (100%) in children younger than 7 years, and loss of appetite (60%), heartburn (52%), and food impaction (48%) in children older than 7 years and adolescents. Regarding the endoscopic findings, 12 (28%) patients had whitish plaques on the esophageal lining, 8 (18.5%) had longitudinal grooves, 2 (4.5%) had concentric rings, 3 (7%) had longitudinal grooves and whitish plaques, and the remaining 18 (42%) had esophageal mucosa with normal appearance. Despite the initial favorable response, 76.7% of patients required more than one course of corticosteroid therapy (systemic or aerosol) and diet (exclusion or elimination of food or elementary allergens). Persistence of eosinophil infiltration was found in some patients despite favorable clinical response. Conclusions: The classic form of EoE typically shows different symptoms according age range. A significant number of patients required more than one treatment cycle to show clinical remission. Endoscopic and histologic improvement was observed; however, eosinophilic infiltration persisted in some patients.